Bringing Relationships out of the Shadows: Relationship Building as a Foundational Social Resource and Mediator of Context - Hoogsteen, T. J. (Advances in Social Sciences Research Journal, 2023)
Leithwood (2017) outlines personal leadership resources (PLR) and Leithwood et al. (2019) claimed these resources can account for a great deal of variation in school leadership practice. In addition, these leadership resources are recognized in several documents related to leadership standards. Although other leadership resources exist, Leithwood (2017) and Leithwood et al. (2019) claim that the PLRs in these documents are included because there is significant evidence to warrant their inclusion. This article, however, provides evidence that the list of personal leadership resources required for successful leadership is incomplete, and neglects to recognize the importance of the ability to build relationships. Moreover, this article attempts to further the argument forwarded by Hoogsteen (2020) that personal leadership resources mediate context and leadership practice, and this is accomplished only through the construction and maintenance of productive relationships with school staff, district personnel, and the community at large.